2022
DOI: 10.3390/nu14224716
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Dietary Patterns in the Secondary Prevention of Cardiovascular Disease after a Nutritional Intervention Program—A Randomized Clinical Trial

Abstract: Individuals with a history of previous cardiovascular events have an increased risk of mortality and morbidity, so adherence to a healthy dietary pattern is essential. We aimed to evaluate and compare dietary patterns between the control and the experimental group from the BALANCE Program. A total of 2360 individuals aged 45 years or older with previous cardiovascular disease were included. The individuals were randomized into two groups: intervention (dietary prescription with nutritional recommendations, nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This relationship increases the risk of developing obesity and other cardiovascular diseases, which may decrease the quality of life in this younger population. In this Special Issue, in the PASOS study, it is shown that a Mediterranean diet with higher fitness status can be related to higher levels of health-related quality of life, independent of the body mass index [11]. Therefore, these results highlight the importance of promoting healthy lifestyles to ensure the subject's wellbeing, including an individual's social, mental, and physical dimensions [12].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This relationship increases the risk of developing obesity and other cardiovascular diseases, which may decrease the quality of life in this younger population. In this Special Issue, in the PASOS study, it is shown that a Mediterranean diet with higher fitness status can be related to higher levels of health-related quality of life, independent of the body mass index [11]. Therefore, these results highlight the importance of promoting healthy lifestyles to ensure the subject's wellbeing, including an individual's social, mental, and physical dimensions [12].…”
mentioning
confidence: 94%
“…Maintaining caloric restriction could be difficult over time and in some specific cases. In this sense, the article in the framework of the BALANCE program focuses on the whole diet, recommending healthier dietary patterns to prevent the development of new cardiovascular events [11]. They observed an improvement in the dietary patterns with higher intakes of fruits and vegetables and a decrease in salted and sugared ultra-processed foods after an intervention.…”
mentioning
confidence: 99%